THE DIFFERENCE IN CRIMINAL THINKING STYLES AND THE DEPTH OF INVOLVEMENT IN CRIMINAL LIFESTYLES WITH REGARD TO THE AGE, RECIDIVISM AND VIOLENCE OF A CRIMINAL OFFENCE - Vrućinić, Žana S. (NBP. Nauka, bezbednost, policija, 2019)
The aim of this study is to determine the differences in criminal thinking styles measured by Psychological Inventory of Criminal Thinking Styles, PICTS (Walters, 1995; 2005), on one hand, and criminal behavioral styles measured by Lifestyle Criminality Screening Form score, LCSF (Walters, White & Denney, 1991) on the other hand, given the age, the violence of crime and recidivism. The sample of this research was made of 126 inmates of Banja Luka Correctional Facility. The results show that younger convicts violate social rules more than the older ones. Convicts who committ violent crimes have higher scores in interpersonal intrusiveness, while convicts who are prone to non-violent crimes have more present discontinuity as a criminal thinking style. Recidivists, unlike un-recidivists, have higher scores in self-indulgence and social rule break, and also have significantly more pronounced criminal thinking styles of mollification, entitlement, superoptimism and discontinuity. Theoretical and practical implications of these findings are discussed. Key words: convicts, criminal thinking styles, behavioral criminal styles